ChemInform Abstract: Synthesis and Characterization of Barium Tetrafluoridobromate(III) Ba(BrF4)2. Issue 12 (March 2015) - Ivlev, Sergey; Sobolev, Vasily; Hoelzel, Markus; Karttunen, Antti J.; Mueller, Thomas; Gerin, Ivan; Ostvald, Roman; Kraus, Florian
Abstract The title compound is synthesized by the reaction of BaF2 with liquid BrF3 under Freon‐113 (PTFE tube, 99% yield).